2017
DOI: 10.15557/jou.2017.0041
|View full text |Cite
|
Sign up to set email alerts
|

Chest wall – a structure underestimated in ultrasonography. Part III: Neoplastic lesions

Abstract: Chest wall neoplasms mainly include malignancies, metastatic in particular. Differential diagnosis should include clinical data; tumor location, extent, delineation; the degree of homogeneity; the presence of calcifications; the nature of bone destruction and the degree of vascularization. The aim of the paper is to present both the benefits and limitations of ultrasound for the diagnosis of chest wall neoplasms. The neoplastic process may be limited to the chest wall; it may spread from the chest wall into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Several studies have reported on bone tumours in other flat bones, like the skull, pelvis, sternum, and ribs [24], [25]. Bone metastases mainly from lung, breast, kidney and prostate cancer, as well as plasma cell myeloma are relatively common bone tumours of the ribs and sternum, while primary malignant bone tumours are rare [24], [25]. The most frequent primary malignant tumour of the ribs and sternum is chondrosarcoma [24], [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported on bone tumours in other flat bones, like the skull, pelvis, sternum, and ribs [24], [25]. Bone metastases mainly from lung, breast, kidney and prostate cancer, as well as plasma cell myeloma are relatively common bone tumours of the ribs and sternum, while primary malignant bone tumours are rare [24], [25]. The most frequent primary malignant tumour of the ribs and sternum is chondrosarcoma [24], [25].…”
Section: Discussionmentioning
confidence: 99%
“…Bone metastases mainly from lung, breast, kidney and prostate cancer, as well as plasma cell myeloma are relatively common bone tumours of the ribs and sternum, while primary malignant bone tumours are rare [24], [25]. The most frequent primary malignant tumour of the ribs and sternum is chondrosarcoma [24], [25]. Less common primary malignant tumours are Ewing sarcoma and Osteosarcoma [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of such tumors are osteolytic. Ultrasound detection of osseous defects is possible only after the damage of the anterior compact substance[9].…”
Section: Discussionmentioning
confidence: 99%